Determinants of physical activity among adults in the United Kingdom during the COVID‐19 pandemic: The DUK‐COVID study - Spence, John C.; Rhodes, Ryan E.; McCurdy, Ashley; Mangan, Amie; Hopkins, Debbie; Mummery, W. Kerry (British journal of health psychology, 2021)
Objectives This study examined the impact of the COVID‐19 lockdown on the physical activity (PA) of UK adults and potential motivational determinants of such behaviour. Design and methods A survey was conducted with 1,521 UK adults recruited through Prolific.co in early June 2020. Along with demographic information, questions assessed current PA, changes in PA modalities (i.e., overall, around the home, for transport, in the workplace, in the local neighbourhood, at recreation/sport facilities) related to the lockdown, and beliefs about capabilities, opportunities, and motivations according to the COM‐B model. A series of logistic regressions were constructed to examine associations between shifts in the PA modalities and the COM‐B components. Results The majority of respondents (57%) had either maintained or increased their levels of PA during the COVID‐19 lockdown. However, the proportion meeting PA guidelines (31%) was low and engagement in sedentary‐related behaviour for both work and leisure increased substantially during the lockdown. The components of the COM‐B model were associated with shifts in PA. In particular, physical opportunity (odds ratios ranging from 1.14 to 1.20) and reflective motivation (odds ratios ranging from 1.11 to 1.25) appeared to be the most consistent predictors of behaviour. Conclusions If UK adults believed they had the physical opportunity and were motivated, they were more likely to have maintained or increased their PA during the COVID‐19 lockdown. However, the majority of adults are not meeting the UK guidelines on PA and the prevalence of PA is substantially lower than national surveys prior to the pandemic. Statement of contribution What is already known on this subject? The COVID‐19 pandemic has significantly disrupted the daily routines of citizens globally. Engagement in physical activity appears to have declined as a result of the requirement to self‐isolate and stay in place. The COM‐B model of behaviour change is a useful framework for identifying the correlates and determinants of behaviour. What does this study add? Though most UK adults maintained or increased their engagement in physical activity during the COVID‐19 pandemic, the majority did not meet recommended guidelines. Reflective processes and physical opportunity were the primary predictors of change in physical activity.